EKSISTENSI TINDAK PIDANA PENIPUAN (BEDROG) DALAM PASAL 378 KUHP DI ERA DIGITAL - Al Miski, Yusran Radyamal; Putra, Satria Manggala; Purwanto, Muhammad Iqbal; Luthfiyyah, Syadza (JOURNAL EQUITABLE, 2025)
The advancement of digital technology has given rise to new and complex modes of fraudulent crime, necessitating an evaluation of the relevance of Article 378 of the Indonesian Criminal Code (KUHP) as a legal basis. This study aims to analyze the compatibility of conventional fraud elements under the KUHP with the characteristics of digital fraud and the challenges in its enforcement. The research employs a normative juridical approach through literature review and case analysis. The findings indicate that while Article 378 KUHP can be applied to digital fraud through broad interpretation, significant challenges remain, including perpetrator anonymity, cross-jurisdictional issues, and the need for digital evidence. Supporting regulations such as the ITE Law and the draft revision of the Criminal Code (RKUHP) play a role in expanding legal protection, yet policy updates are required to address legal gaps. The study concludes that Article 378 KUHP remains relevant but requires adaptation through dynamic interpretation and harmonization with specialized cybercrime regulations.